Global Similarities and Multifaceted Differences in the Production of Partner-Specific Referential Pacts by Adults with Autism Spectrum Disorders - Nadig, Aparna; Seth, Shivani; Sasson, Michelle (Frontiers in Psychology, 2015)
Over repeated reference conversational partners tend to converge on preferred terms or referential pacts. Autism spectrum disorders (ASD) are characterized by pragmatic difficulties that are best captured by unstructured tasks. To this end we tested adults with ASD who did not have language or intellectual impairments, and neurotypical comparison participants in a referential communication task. Participants were directors, describing unlexicalized, complex novel stimuli over repeated rounds of interaction. Group comparisons with respect to referential efficiency showed that directors with ASD demonstrated typical lexical entrainment: they became faster over repeated rounds and used shortened referential forms. ASD and neurotypical groups did not differ with respect to the number of descriptors they provided or the number of exchanges needed for matchers to identify figures. Despite these similarities the ASD group was slightly slower overall. We examined partner-specific effects by manipulating the common ground shared with the matcher. As expected, neurotypical directors maintained referential precedents when speaking to the same matcher but not with a new matcher. Directors with ASD were qualitatively similar but displayed a less pronounced distinction between matchers. However, significant differences emerged over time; neurotypical directors incorporated the new matcher’s contributions into descriptions, whereas directors with ASD were less likely to do so.